Effectiveness of universal school-based mindfulness training compared with normal school provision on teacher mental health and school climate: results of the MYRIAD cluster randomised controlled trial - Kuyken, W; Ball, S; Crane, C; Ganguli, P; Jones, B; Montero-Marin, J; Nuthall, E; Raja, A; Taylor, L; Tudor, K; Viner, RM; Allwood, M; et al. (BMJ, 2022)
Background Education is broader than academic teaching. It includes teaching students social–emotional skills both directly and indirectly through a positive school climate.